Efek Pemberian Formula Tepung Mocaf, Kacang Merah Dan Ikan Bandeng Untuk Balita Gizi Kurang Di Puskesmas Sabokingking - Delmi, Zahroh Istantini; Podojoyo, Podojoyo; Muzakar, Muzakar; Nazarena, Yunita; Sriwiyanti, Sriwiyanti (JGK: Jurnal Gizi dan Kesehatan, 2022)
Background : One of the nutrition major problems in Indonesia is malnutrition. Age <5 years is a very important period in the process of child development. Therefore, during this period, child nutritional intake and health care must be considered . Purpose : To see the effect of giving biscuits formula of mocaf, red bean, and milkfish flour on the body weight of undernourished children at the Sabokingking Health Center. Methods : This research was conducted in 2 stages. In the first stage, it uses an experimental research type with a completely randomized non-factorial design. Then the second stage uses a quasi-experimental type of research with pre-test and post-test designs with two groups. This research was conducted in January-April 2022 at the Sabokingking Health Center with a total sample of 30 children under five in each group, which was determined by a non-random method based on inclusion criteria. Results : The results of the Independent T-Test showed that there was no significant difference in the average weight gain in the treatment and comparison groups with a p-value of 0.15 (> 0.05). Conclusion : There is no effect of giving the formulated cookies to the body weight of children under 5.